Development of Digital Student Worksheet Based on Process Differentiation with STEM-PjBL Approach on Light Wave Material - Sekarningrum, Miranti; Ellianawati, Ellianawati; Subali, Bambang; Linuwih, Suharto; Nugultham, Kulthida (STKIP Singkawang, 2025)
The independent curriculum employs a differentiated approach to learning. The differentiation approach is employed to adjust the ability of students to comprehend the material. One model that can be applied is the PjBL model, which is integrated with STEM. Learners will engage in problem-solving activities in the context of physics education, utilizing technology as a tool. The integration of the model with the learning media employed is a harmonious process. Digital student worksheets represent a potential solution for the integration of the STEM-PjBL model. This research is a development research (RnD) project that employs the ADDIE development model. The development of digital student worksheets is comprised of three stages: analysis, design, and development. The analysis stage involves determining the characteristics of digital student worksheets. The design stage entails designing content for digital student worksheets. Finally, the development stage aims to obtain validation of feasibility and practicality from experts. The results of the validation of material and media experts indicate that digital student worksheet is suitable for use with revisions. The results of the practicality test of digital worksheets by teachers indicate that they are feasible, while the results of the test by students indicate that they are very feasible.